Reconstructing identities among Santhal: An anthropological perspective - Kadariya, Om Nath (SADGAMAYA, 2024)
This study of evolving identities is based on instrumental approach in a way that present identities are the product of historical forces and situations as the culture and society of Santhal from Haldibari Rural Municipality have always been in the form of evolution and acceptance of changing realities. It explains the changes seen in the origin, shifting nature, and their agentive space with resistance which has helped to create new space in their own life. This research is in quest of the ways of evolution of Santhal identities and their transforming relations due to various causes. It has uncovered Santhal of their ‘being’ and their subjective experiences as Santhal in the more significant eastern part of Tarai Nepal, particularly in Haldibari Rural Municipality.